Can’t Help Lovin’:David Chidester’s Pop Culture Colonialism - Kathryn Lofton (Journal for the Study of Religion)
This article examines the likability ofhip-hop star Kanye West and The Voicechampion Jordan Smith to explain the colonial terms for our pop culture taste. The writings of David Chidester establish the tie between religion and colonialism as an axiomatic one; he also argues that popular culture is a rich site for formations of religion. West and Smith offer an opportunity to argue the connection between these two strands of scholarly observance, showing the fractal effects of colonialism in Africa on the preferences of pop culture consumption in America.The attraction to West’s unlikability is the other side of the easy adorationfor Jordan Smith: like those colonists who gave religion to those colonized subjects they dominated, pop consumers refuse to admit their intimate and needful connection to those idols who resist theircontrol. Although organized by particular instances, this article seeks to encourage those in pop culture studies to see the erotic work of dislike; it seeks to encourage those in religious studies to see how pop subjects carryforward the classificatory imprints of colonial frontiers